HR Performance Improvement Model Through the SECI Process - Dita Prameswari; Novi Nuryani (LPPM Universitas An Nuur, 2022)
Background: In the era of knowledge-based economy and business model 4.0, the performance of human resources (HR) is one of the components for Find out how your business is growing. To improve business sustainability it is important to pay attention to the knowledge creation process to improve human resource performance. In the knowledge creation process, members of the organization not only receive knowledge but also must have good knowledge absorption capacity. This needs to be encouraged by the existence of a leadership role.Purpose: The purpose of this research is to develop the main concepts that are believed to improve the HR Performance. This concept is the SECI process and is supported by two other concepts, namely altruistic leadership and absorptive capacity.Methods: The research method used is a literature survey to define concepts and develop measurements.Results: The results of the study found a construct in an effort to improve HR performance, namely through the new concept of the SECI process which is supported by the intervening variables altruistic leadership and absorptive capacity.Conclusion: HR performance will increase if the company applies it SECI processes in knowledge creation activities. The SECI process will be more effective and efficient with the application of altruistic leadership and absorptive capacity. Thus the efforts made are for the progress of the company in the long term.Suggestion: For the future agenda we plan to validate the measurement of the concepts and test the proposed model with quantitative methods.